First-Time Voters' Views on Political Parties in the Lead-up to the 2024 General Election in Probolinggo City - Siti Marwiyah; Veronica Sri Astuti Nawangsih; Siti Ulfa Nuraini (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2026)
Introduction/Main Objectives: In a democratic country, general elections are a tangible manifestation of the system of government. The existence of political parties in a democratic country is considered essential for the order of modern national life, as they serve as effective means of communication, both vertically and horizontally. Background Problems: First-time voters, consisting of Indonesian citizens aged 17 or older or who are married, often show high enthusiasm for participation, even though they may not yet have a firm political preference. This makes them a group of undecided voters, as their decisions are more influenced by local political conditions than by specific ideologies. Research Methods This study uses a descriptive quantitative approach to analyze first-time voters' perceptions of political parties. A total of 84 respondents participated in data collection via questionnaire, with research variables including values, beliefs, experiences, and knowledge. The sampling technique used was purposive samplingvv. Finding/Results: The research results show that political parties have adopted Pancasila values, are trustworthy in channeling public aspirations, are actively involved in community activities, and have a good understanding of their vision, mission, and work programs. Conclusion: Young people tend to view political parties' performance positively, particularly in implementing the principles of Pancasila, which recorded the highest average score compared to other aspects. Other variables such as level of trust, political experience, and understanding of the political system also showed significant results.